Critical success factors of TQM for sustainability in higher education institutions: A theoretical contribution - Nogueiro, T.; Saraiva, M.; Pires, A. R. (Quality Innovation and Sustainability. ICQUIS 2022. Springer Proceedings in Business and Economics, 2023)
Total quality management (TQM) is a management approach that was initially used by the industry, but that over time has been adapted to other types of institutions, including higher education institutions (HEI). Currently, the topic of TQM associated with HEIs and higher education is certainly no longer a novelty. However, considering the competitiveness of these institutions for the best students, best researchers, and best means, the sustainability of these institutions has become almost a requirement. This chapter intends to analyze the critical success factors (CSF) in the implementation of total quality management and the critical success factors for sustainability in HEI as a way of contributing to a theoretical reflection on the sustainability of higher education. This work was based on the 11 CSFs for the implementation of TQM, following the studies of Bayraktar et al. (Total Quality Management 19:551–574, 2008), corroborated/validated by Nadim and Al-Hinai (International Journal of Applied Sciences and Management 1:147–156, 2016), in HEI: leadership, vision, measurement and evaluation, process control and improvement, program design and resources, quality system improvement, employee involvement, recognition and reward, education and training, student focus, and other stakeholders’ focus. After identifying the keywords or phrases of the CSFs in TQM implementation, we identified many other aligned CSFs for a better understanding of the critical success factors for sustainability implementation in HEIs.